Combo Robot Reviews for Techomech Inspection - Kanniga , E.; Malik, Mohamed (International Journal of Psychosocial Rehabilitation, 2019)
Sophisticated electronics from more conventional pigs such as cleaning (i.e., poly, brush, bullet, etc.), gauging, or batch pigs that are simple mechanical devices run in pipelines for various purposes. Existing technologies for inspecting pipelines and other things, such as the human body, are surveyed. A sensor that could record multiple data types, such as temperature, pressure, acceleration, flow, and distance, and store them on the unit was selected and adapted for use in pipelines.